Triterpenes from maytenus macrocarpa and evaluation of their anti-hiv activity - Piacente, Sonia; Dos Santos, Lourdes Campaner [UNESP]; Mahmood, Naheed; Pizza, Cosimo (SAGE Publications, 2006)
A set of pentacyclic triterpenes has been isolated from the bark of Maytenus macrocarpa (Celastraceae). It includes two new olean-12-ene derivatives, namely 3β, 22α-dihydroxy-olean-12-en-30-oic acid (1) and 22α-hydroxy-olean-12-en-3-oxo-30-oic acid (2), and the new urs-12-ene derivative 3-(E)-coumaroyluvaol (7), along with 10 known compounds possessing olean-12- ene, urs-12-ene, lupane and friedelane skeletons. The structures have been elucidated by extensive spectroscopic methods including 1D- and 2D-NMR experiments, as well as ESI-MS analysis. All isolated compounds were tested for anti-HIV activity in C8166 cells infected with HIV-1MN. The most active compound was 22α-hydroxy-12-en-3-oxo-29-oic acid (triterpenonic acid A, 4), with an EC50 value of 1 μg/mL and a selectivity index of 35.
Keywords: Anti-HIV activity; Celastraceae; Maytenus macrocarpa; Pentacyclic triterpenes